Diet to improve nutritional status in preschoolers - Risna Ayu Rahmadani; Trimaya Cahya Mulat; Maria Kurni Menga; Darmi Arda (Jurnal Edukasi Ilmiah Kesehatan, 2024)
Introduction Preschoolers are a group that is vulnerable to malnutrition. Inadequate nutritional conditions at this stage of development can seriously impact their growth, development, and long-term health. Therefore, proper handling and appropriate dietary strategies are essential to improving the nutritional status of preschoolers. Objective presents an overview of diets that can improve nutritional status in preschoolers. Methods: This type of research is a quantitative cross-sectional study approach. The population in this study was preschool-age children (3-6 years) found in Kanita Tiara Islamic Kindergarten, which amounted to 78 children obtained by totality or using the whole sampling method. Collection of information using food frequency questionnaires and mechanical measurements. Results show that p = 0.015 < p = 0.05, meaning a relationship exists between diet and nutritional status in preschool-aged children. Conclusion: Diet affects nutritional status in preschool-aged children. Dietary strategies applied to preschoolers should pay attention to their nutritional needs and environmental factors that affect their diet. With a holistic and sustainable approach, it can be expected that the nutritional status of preschoolers can be improved, providing a solid foundation for their optimal health and development.